Possibilidades de boas práticas no ensino de Matemática nos anos iniciais do Ensino Fundamental: uma revisão sistemática da literatura - Madormo, Rita de Cássia Domingues (2022)
This Systematic Literature Review contemplates the brazilian academic production that addresses possible successful experiences of teachers who teach mathematics in the early years of elementary school and its relations with teacher education. The research is justified by the need to reflect on the possible practices on this issue, considering that in face of the demands of an increasingly complex society, teachers are challenged to develop new skills for teaching, especially within this area of science. The results for analysis was obtained through a survey of theses and dissertations catalogued in the CAPES Theses and BDTD. The theoretical references contemplate studies on the teaching of mathematics in the early years of elementary school and on the training of teachers who teach mathematics in these years. The adopted framework revealed that the initial training courses for early years teachers, in general, do not offer a solid mathematics education. The analysis of the full texts of dissertations and thesis was inspired by the methodological framework of content analysis according to the perspective of Bardin (2016). The research results consists of a set of 20 papers (16 dissertations and 4 thesis), which were read in full, seeking the identification of thematic axes for the analysis process. The analyses showed the teachers commitment to the students learning, to the contextualization of the themes studied, to the students' motivation and interest in the construction of mathematical concepts, and also pointed to the valorization of professional development. With regard to math teaching practices, the importance of the repetition of exercises, the lecture class, and the use of textbooks were highlighted, indicating the permanence of practices consolidated throughout history in the teaching of this subject. On the other hand, there are also breaks with memoristic teaching and an appreciation of the collective construction of mathematical knowledge, by indicating the practice of group work, in which students are challenged to reason and discuss their hypotheses with their classmates. The results so reveal that successful experiences result from the teacher's involvement with the improvement of his teaching practice, learning in practice the knowledge of the art of teaching. Even though we are concerned about seeking new methods and bringing mathematical knowledge closer to the new teaching proposal that requires the use of new languages and technologies, we suggest that successful teaching is based on an epistemology of practice and is understood as a process of acting and thinking right in the classroom, of making wise decisions when faced with the unforeseen, and of choosing alternative ways to teach content and interact with students